Literacy under the perspective of Paulo Freire (Research, Society and Development, 2021)
This theoretical essay aimed to discuss the literacy process based on the concept of liberating education of the renowned educator Paulo Freire, with a view to elucidating the important role of the school in the formation of the conscious subject, since, according to his conception, literacy and awareness are not separate. This is a study in the form of a theoretical essay. Literacy deserves to be highlighted, as it is the initial field of Freire's work, and also, because it is a theme that instigates several reflections in Brazil, a country with a high number of illiterate youth and adults. In this sense, actions aimed at the literacy of these young people and adults, more than a social and political issue, are historical and cultural. The relevance and timeliness of Paulo Freire's philosophy has been present at all levels of education since its inception, so that throughout the text some terms have been improved, as well as research data cited have been updated.